PRELIMINARY BIOGEOCHEMICAL DATA ON MICROBIAL CARBONATOGENESIS IN ANCIENT EXTREME ENVIRONMENTS (KESS-KESS MOUNDS, MOROCCO) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2013)
The Devonian Kess-Kess mounds, cropping out in the Hamar Laghdad Ridge (SE Morocco), provide a useful case-study for understanding the relationships between the microbial metabolic activities and micrite precipitation in an extreme environment. Very fine dark and white wrinkled laminae record microbial activity and the geochemistry of the organic matter allows the  characterization of the source organisms. The biogeochemical characterization of extracted organic matter was performed through the functional group analyses by FT-IR Spectroscopy. FT-IR parameters indicate a marine origin and low thermal evolution for the organic material. The organic matter is characterized by the presence of stretching ?C=C vibrations attributable to alkene and/or unsaturated carboxylic acids. Preliminary analysis with GC-MS provides evidence for an autochthonous (
Keywords: Carbonatogenesis; microbialites; extreme environments; mud mounds; Morocco; Astrobiology